Protective effect of a mixture of kefir-isolated lactic acid bacteria and yeasts in a hamster model of Clostridium difficile infection - Bolla, Patricia Araceli (2013)
The objective of this work was to test the protective effect of a mixture (MM) constituted by kefir-isolated microorganisms (Lactobacillus plantarum, Lactobacillus kefir, Lc. lactis, Kluyveromyces marxianus and Saccharomyces cerevisiae) in a hamster model of infection with Clostridium difficile, an anaerobic Gram-positive bacterium that causes diarrhoea. Placebo or MM was administered ad libitum in drinking water from day 0 to the end of treatment. Hamsters received orally 200 μg of clyndamicin at day 7 and then were infected with 1 × 108 CFU of C. difficile by gavage. Development of diarrhoea and death was registered until the end of the protocol. Surviving animals were sacrificed at day 16, and a test for biological activity of clostridial toxins and histological stainings were performed in caecum samples. Six of seven infected animals developed diarrhoea and 5/7 died at the end of the experimental protocol. The histological sections showed oedema and inflammatory infiltrates with neutrophils and crypt abscesses. In the group of animals infected and treated with MM1/1000, only 1 of 7 hamsters showed diarrhoea and none of them died. The histological sections showed only a slight thickening of the mucosa with presence of lymphocytic infiltrate. These results demonstrate that an oral treatment with a mixture of kefir-isolated bacteria and yeasts was able to prevent diarrhoea and enterocolitis triggered by C. difficile.